COMPUTER EFFICACY TRAINING AND COGNITIVE BEHAVIOUR THERAPY IN THE MANAGEMENT OF COMPUTER ANXIETY AMONG (2016)
Computer anxiety has been identified as a prominent drawback to many freshmen in the Open and Distance Learning (ODL) institutions in Nigeria. It is a known fact that inadequate computer skills coupled with computer anxiety are linked to attrition rate and poor academic performance among distance learners who by exigency should utilise computer to bridge the transactional and interactional distance that exist between them, their tutors and other relevant personnel. This is capable of jeopardising learners‘ adjustment, performance and general coping capacity. There is a plethora of studies on computer anxiety with little attention to intervention that could reduce the menace among ODL students. This study, therefore, determined the effectiveness of Computer Efficacy Training (CET) and Cognitive Behaviour Therapy (CBT) in the management of computer anxiety among National Open University of Nigeria (NOUN) freshmen in Southwestern Nigeria. The moderating effects of age and gender were examined. Technology Acceptance Model provided the framework for the study while the pretest-posttest control group quasi-experimental design with a 3x2x2 factorial matrix was adopted. Three study centres of NOUN (Akure, Ibadan and Lagos) were randomly selected from the nine study centres of the university in Southwestern Nigeria. Eighty-five computer anxious freshmen who met the screening criteria were randomised into CET (30), CBT (25) and Control (30) groups. The interventions lasted eight weeks. The Computer Anxiety Scale Revised (α=0.89) with the norm of 60.0 was utilised for screening. Computer Anxiety Rating Scale (α =0.86) was used to measure the criterion variable. These were complemented by CET and CBT training guides. Analysis of covariance and Scheffe post-hoc test were utilised for data analysis at 0.05 level of significance. Participants‘ mean age was =29.69, with 56.5% females. There was a significant main effect of treatments on the management of computer anxiety of NOUN freshmen (F (2, 72)= 19.772, η2 = 0.355). Participants in the CBT ( =31.00) had the least computer anxiety compared to those in CET ( =33.10) and the control ( =38.07) groups. There was a significant main effect of age(F (1, 72)= 8.927, η2 = 0.110)on computer anxiety. The older NOUN freshmen ( = 34.15) significantly benefited more than younger NOUN freshmen ( = 44.27). There was no significant main effect of gender on computer anxiety.There were no two-way interaction effects of treatment and age and treatment and gender on computer anxiety. The three-way interaction effects of treatment, age, and gender was also not significant. Computer efficacy training and cognitive behaviour therapy were effective in managing computer anxiety of National Open University freshmen in Southwestern Nigeria. Educational and counselling psychologists should largely adopt cognitve behaviour therapy in the reduction of computer anxiety and service providers should take cognisance of age in computer appreciation training for open distance learning students. Keywords: Computer efficacy training, Cognitive behaviour therapy, Computer anxiety, National Open University of Nigeria Word count: 454